From deficient civilian accommodation to the political governance of defense: Strategic planning in the defense sector of Argentina, 2015-2021 - Anzelini, Luciano (2023)
Since the return to democracy, Argentina has witnessed two stages with respect to defense priorities. In the first stage, which lasted 20 years, civilian control of the armed forces dominated the agenda, while the management of strategic areas was postponed. During the second stage, the institution of the Cycle of Planning of National Defense (CPDN) in 2007 signaled an inflection point that granted political authorities with the tools for taking on strategic areas; however, the empowerment of civilians sparked marches and countermarches. This article covers the management of defense between 2015 and 2021, with the aim of analyzing sectorial strategic planning and actions implemented in relation to the CPDN during the governments of Mauricio Macri (2015-2019) and Alberto Fernández (2019-2021). Methodologically, the study is qualitative-comparative, and it is based on primary and secondary sources and interviews with key actors. It is concluded that the administration of Cambiemos (2015-2019) reflects a case of “deficient civilian accommodation.” By contrast, during the first half of the government of Alberto Fernández a “political government of defense” advanced, as evidence shows a firm governance will for the exercise of this mandate; expertise in the political ranks and technicians of the ministry for supervising the CPDN; and operating capacity for implementing the defined policies.